2016
DOI: 10.12966/abc.02.01.2016
|View full text |Cite
|
Sign up to set email alerts
|

Blue Whale (Balaenoptera musculus) Behavior and Group Dynamics as Observed from an Aircraft off Southern California

Abstract: Group behavior and interactions of endangered blue whales (Balaenoptera musculus) have not been systematically studied. Such behavioral data are often overlooked when assessing anthropogenic effects. Yet behavioral data are necessary to compare "normal" behaviors with behavior affected by anthropogenic factors of concern relative to effective management and recovery of blue whales. For a baseline study, we hypothesized that the response variables sighting rate, group size, calf presence and group cohesion (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…A similar process could be driving the observed differences between male blue and fin whales. Alternatively, blue whales are known to engage in social behavior while in southern California (Lomac-MacNair and Smultea, 2016). Visual inspection of the tag records revealed that many dives made by individuals of both species during the circuits of offshore waters had the characteristics of dives made while whales are vocalizing (shallow, flat-bottomed, minimal acceleration; see Calambokidis et al, 2007;Oleson et al, 2007;Stimpert et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A similar process could be driving the observed differences between male blue and fin whales. Alternatively, blue whales are known to engage in social behavior while in southern California (Lomac-MacNair and Smultea, 2016). Visual inspection of the tag records revealed that many dives made by individuals of both species during the circuits of offshore waters had the characteristics of dives made while whales are vocalizing (shallow, flat-bottomed, minimal acceleration; see Calambokidis et al, 2007;Oleson et al, 2007;Stimpert et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…, Campbell et al . , Lomac‐MacNair and Smultea ). This timing matches the presence of blue whale sounds in passive acoustic recordings from the SCB: D calls are typically recorded from April through November, with a peak in August, while A and B call types appear in recordings in June and continue through January, peaking in September and October (Oleson et al .…”
mentioning
confidence: 99%
“…An additional question is whether geographic setting also results in different calling behavior. Lomac‐MacNair and Smultea () observed that behavioral state, group type and group size of blue whales off southern California varies with distance from shore. These findings, coupled with other behavioral trends such as increased singing observed from solitary males traveling offshore (Oleson et al .…”
mentioning
confidence: 99%
“…Marine mammals inhabit a vast array of habitats and as a result threats from HIREC are myriad. It is also important to consider the spatio-temporal scale of the species in question when assessing changes in behavior as a result of environmental factors (Lomac-Macnair and Smultea, 2016).…”
Section: Consequences Of Environmental Changes On Behaviormentioning
confidence: 99%